Działalność Komisji Badań nad Antykiem Chrześcijańskim TN KUL w roku akademickim 2023/2024 - Głowa, Anna; Szynkowski, Marek; Szkopiński, Maciej; Głowacki, Paweł (Vox Patrum, 2024)
Activity of the Committee for Research on the Christian Antiquity of the Learned Society KUL in the Academic Year 2023/2024